Folic Acid and Vitamin B12 Supplementation Improves Coronary Flow Reserve in Elderly Subjects with Vitamin B12 Deficiency - YILMAZ, YUSUF (ELSEVIER SCIENCE INC, 2010)
Background and Antic. Major cardiovascular risk factors including hyperhomocystememia are frequently associated with decreased corollary flow reserve (CFR), an important physiological parameter of the corollary circulation This study was desiened to determine whether folate (5 mg) and vitamin B12 (500 mu g) supplementation in elderly patients with vitamin B12 deficiency improved CFR, while reducing homocysteme levels. Methods. Forty-four patients aged >65 years showing serum vitamin B12 concentrations <180 mg/dL were randomized to take either oral folate (5 me.) plus vitamin B12 (500 mu g) supplementation = 24) or placebo (n = 20) for 8 weeks. The study course consisted of two visits: visit 1 (pretreatment) included the baseline assessment of laboratory profile and CFR values with trans-thoracic Doppler echocardiography Visit 2 was scheduled 8 weeks later to repeat CFR and laboratory tests after therapy. Results. In the treatment arm. oral supplementation with folatc and vitamin B12 significantly improved total cholesterol, serum folate, serum vitamin B12, homocysteine, and insulin resistance. At 8 weeks, the treatment group had a significant increase from baseline in CFR values (baseline 17 +/- 0 2, posttreatment 2 1 +/- 0.2,p <0 001) that was not seen in the placebo group (baseline: 1.6 +/- 0.2, posttreatment: 1.6 +/- 0 2, P = ns). Conclusions. In this study of elderly subjects with vitamin B12 deficiency, supplementation with folate and vitamin B12 was associated wall a significant improvement CFR values (C) 2010 IMSS Published by Elsevier Inc.
Keywords: Folale; Vitamin B12; Homocysteine; Echocardiography; Corollary flow reserve; CARDIOVASCULAR-DISEASE; ENDOTHELIAL FUNCTION; PLASMA HOMOCYSTEINE; B-VITAMINS; HYPERHOMOCYSTEINEMIA; ATHEROSCLEROSIS; EVENTS; FOLATE; LEVEL